2016
DOI: 10.1111/jai.13192
|View full text |Cite
|
Sign up to set email alerts
|

New record and range extension of the big-scale sand smeltAtherina boyeriRisso, 1810 (Atherinidae) in the Devegecidi Dam Lake, Tigris River basin, Turkey

Abstract: The big-scale sand smelt, Atherina boyeri, is recorded from the Devegecidi Dam Lake in 2016, the first record of this invasive species in the Tigris River basin, with potential to extend to all countries in the Middle East. The smelts were caught with a trawl net mesh size of 6 mm. The captured specimens are described and compared. Records of A. boyeri from Turkish inland waters are summarised from the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A. boyeri is tolerant of a wide range of salinities which expand their habitats to different environments from coastal estuarine waters to freshwater habitats (Freyhof & Kottelat, 2008). The presence of A. boyeri in several freshwater environments in Türkiye has been reported previously (Kırankaya et al 2014;Saç et al 2015;Apaydın Yağcı et al 2015;Gençoğlu & Ekmekçi 2016;Ünlü et al 2017;Partal et al 2019;Ağdamar et al 2021;Kale et al 2022).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…A. boyeri is tolerant of a wide range of salinities which expand their habitats to different environments from coastal estuarine waters to freshwater habitats (Freyhof & Kottelat, 2008). The presence of A. boyeri in several freshwater environments in Türkiye has been reported previously (Kırankaya et al 2014;Saç et al 2015;Apaydın Yağcı et al 2015;Gençoğlu & Ekmekçi 2016;Ünlü et al 2017;Partal et al 2019;Ağdamar et al 2021;Kale et al 2022).…”
Section: Introductionmentioning
confidence: 67%
“…A. boyeri has translocated species and has been sighted in many dam lakes in Türkiye (Altındağ & Ahiska 2006;Gaygusuz et al 2006;Tarkan et al 2007;Becer-Ozvarol & Karabacak 2011;Ünlü et al 2017;Kale et al 2022), though until now there had not been a confirmed record for any fish species in Reyhanlı Dam Lake. Therefore, the present study aimed to present a new distribution area of A. boyeri along with some biological and fishery parameters from Reyhanlı Dam Lake.…”
Section: Introductionmentioning
confidence: 99%
“…Because primarily native species were targeted by the underlying surveys, the distribution of non‐native species (especially in the Euphrates catchment) remained anecdotally described. For example, C. carpio , Carassius carassius , C. gibelio and Oncorhynchus mykiss were recorded in the Atatürk Reservoir located in the Euphrates River (Bayhan, 2021), Xiphophorus hellerii and Poecilia reticulata are known for the upper Euphrates catchment (Kırankaya & Ekmekçi, 2021), H. fossilis is known to occur in the Tigris catchment (Kaya et al, 2016), and Atherina boyeri was described from the Devegeçidi Reservoir (Ünlü et al, 2017). However, these species did not occur in the collection material analysed, emphasizing the prevailing threat presented by lacking or anecdotal information on community compositions.…”
Section: Discussionmentioning
confidence: 99%
“…This species has economic value, however, it is regarded as translocated/invasive species for the inland waters of Turkey. In recent years, it was introduced to many natural and artificial lakes in Turkey for fish stocking in those areas (Saç et al, 2015;Ünlü et al, 2017;Partal et al, 2019). Because of the wide variety of food and habitat preferences, this species is very well adapted to the environment it enters, grows rapidly and creates large populations.…”
Section: Discussionmentioning
confidence: 99%